SELECTION OF A SOLAR COOLING SYSTEM FOR STRAWBERRY STORAGE IN THE SOUTH OF BRAZIL - Soares, L. D. M.; Mendiburu, A. A. Z.; Rodrigues, L. J. (Revista de Engenharia Térmica, 2024)
Solar energy is an alternative to reducing dependence on non-renewable energy sources in various productive sectors. The present work has its main objective to simulate, evaluate and select a solar cooling system using a double absorption cycle (H2O – LiBr). The heat source of the generator-absorber is the water heated through different technologies of solar thermal collectors: Evacuated Tube Collector (ETC) and Parabolic Trough Collector (PTC). Five different arrangement areas were tested for each collector type. The systems were simulated in the TRNSYS® software. A 334.4 m³ cold chamber must be maintained at a constant temperature of 0 ºC. The thermal and energy analysis results indicate that the ETC configuration has the best system efficiency and the highest solar fraction throughout the year. The best option evaluated is the ETC configuration with a collector area of 100 m². In addition to supplying the thermal demand, it presents the most significant collector efficiencies, a better solar ratio, the highest savings at the end of the analysis period, and the lowest required investment value, showing as a sustainable option.